Posttraumatic Propofol Neurotoxicity Is Mediated via the Pro–Brain-Derived Neurotrophic Factor-p75 Neurotrophin Receptor Pathway in Adult Mice*. Issue 2 (February 2016) - Sebastiani, Anne; Granold, Matthias; Ditter, Anja; Sebastiani, Philipp; Gölz, Christina; Pöttker, Bruno; Luh, Clara; Schaible, Eva-Verena; Radyushkin, Konstantin; Timaru-Kast, Ralph; Werner, Christian; Schäfer, Michael K.; et al.
Abstract : Objectives: The gamma-aminobutyric acid modulator propofol induces neuronal cell death in healthy immature brains by unbalancing neurotrophin homeostasis via p75 neurotrophin receptor signaling. In adulthood, p75 neurotrophin receptor becomes down-regulated and propofol loses its neurotoxic effect. However, acute brain lesions, such as traumatic brain injury, reactivate developmental-like programs and increase p75 neurotrophin receptor expression, probably to foster reparative processes, which in turn could render the brain sensitive to propofol-mediated neurotoxicity. This study investigates the influence of delayed single-bolus propofol applications at the peak of p75 neurotrophin receptor expression after experimental traumatic brain injury in adult mice. Design: Randomized laboratory animal study. Setting: University research laboratory. Subjects: Adult C57BL/6N and nerve growth factor receptor–deficient mice. Interventions: Sedation by IV propofol bolus application delayed after controlled cortical impact injury. Measurements and Main Results: Propofol sedation at 24 hours after traumatic brain injury increased lesion volume, enhanced calpain-induced αII-spectrin cleavage, and increased cell death in perilesional tissue. Thirty-day postinjury motor function determined by CatWalk (Noldus Information Technology, Wageningen, The Netherlands) gait analysis was significantly impaired in propofol-sedated animals. Propofol enhanced pro–brain-derived neurotrophic factor/brain-derived neurotrophic factor ratio, which aggravates p75 neurotrophin receptor–mediated cell death. Propofol toxicity was abolished both by pharmacologic inhibition of the cell death domain of the p75 neurotrophin receptor (TAT-Pep5) and in mice lacking the extracellular neurotrophin binding site of p75 neurotrophin receptor. Conclusions: This study provides first evidence that propofol sedation after acute brain lesions can have a deleterious impact and implicates a role for the pro–brain-derived neurotrophic factor-p75 neurotrophin receptor pathway. This observation is important as sedation with propofol and other compounds with GABA receptor activity are frequently used in patients with acute brain pathologies to facilitate sedation or surgical and interventional procedures.